Sonic metamaterials: Reflection on the role of topology on dispersion surface morphology. (15th October 2017) - Gorshkov, V.N.; Navadeh, N.; Sareh, P.; Tereshchuk, V.V.; Fallah, A.S.
Abstract: Investigating dispersion surface morphology of sonic metamaterials is crucial in providing information on related phenomena as inertial coupling, acoustic transparency, polarisation, and absorption. In the present study, we look into frequency surface morphology of two-dimensional (2D) metamaterials of K3, 3 and K6 topologies. The elastic structures under consideration consist of the same substratum lattice points and form a pair of sublattices with hexagonal symmetry. We show that, through introducing universal localised mass-in-mass phononic microstructures at lattice points, six single optical frequency-surfaces can be formed with required properties including negative group velocity. Splitting the frequency-surfaces is based on the classical analog of the quantum phenomenon of 'energy-level repulsion', which can be achieved only through internal anisotropy of the nodes and allows us to obtain different frequency band gaps. Graphical abstract: Highlights: Dispersion surface morphology of 2D sonic metamaterials of K3, 3 and K6 topologies is investigated. Effective methods for creating and manipulating band gaps are proposed based on anisotropic lattice acoustic properties. Separation of acoustic surfaces from optical surfaces is connected with negative effective mass in lattice unit shells. Effective vibration coupling requires internal masses to be of the same order as or higher order than external masses. Negative group velocity over a significant part of the Brillouin zone may be realised for an optical dispersion surface.